Наукова спадщина О.О. Русова в контексті актуальних проблем української етнології - Скрипник, Г. (Народна творчість та етнографія, 2007)
У лютому виповнилося 160 років з дня народження відомого вченого, етнографа, статистика та громадського діяча Олександра Русова. This article is devoted to the famous scholar, ethnographer, civil activist Oleksandr Rusov. All his work was concentrated on the study of Ukrainian folk, their history, life style and language. Among his most prominent works was the foundation of the statistics as the scholarly discipline and its use for the ethnographical studies. Special attention deserves his work “The Statistics of the Ukrainian Population of the European Russia”. His data on Ukrainian and Russian population in various regions at different historical times are very valuable for the contemporary scholars. He actively participated in Ukrainian cultural life: he was the organizer of the first Ukrainian plays on Kyiv stages, the editor of Prague edition of “Kobzar”, and participated in different social and cultural organizations.